The Sox9 transcription factor determines glial fate choice in the developing spinal cord - Stolt, C. Claus (Cold Spring Harbor Laboratory Press, 2003)
The mechanism that causes neural stem cells in the central nervous system to switch from neurogenesis to gliogenesis is poorly understood. Here we analyzed spinal cord development of mice in which the transcription factor Sox9 was specifically ablated from neural stem cells by the CRE/loxP recombination system. These mice exhibit defects in the specification of oligodendrocytes and astrocytes, the two main types of glial cells in the central nervous system. Accompanying an early dramatic reduction in progenitors of the myelin-forming oligodendrocytes, there was a transient increase in motoneurons. Oligodendrocyte progenitor numbers recovered at later stages of development, probably owing to compensatory actions of the related Sox10 and Sox8, both of which overlap with Sox9 in the oligodendrocyte lineage. In agreement, compound loss of Sox9 and Sox10 led to a further decrease in oligodendrocyte progenitors. Astrocyte numbers were also severely reduced in the absence of Sox9 and did not recover at later stages of spinal cord development. Taking the common origin of motoneurons and oligodendrocytes as well as V2 interneurons and some astrocytes into account, stem cells apparently fail to switch from neurogenesis to gliogenesis in at least two domains of the ventricular zone, indicating that Sox9 is a major molecular component of the neuron–glia switch in the developing spinal cord.